Mice with reduced brain-derived neurotrophic factor expression show decreased choline acetyltransferase activity, but regular brain monoamine levels and unaltered emotional behavior - Chourbaji, Sabine; Hellweg, Rainer; Brandis, Dorothee; Zörner, Björn; Zacher, Christiane; Lang, Undine; Henn, Fritz A.; Hörtnagl, Heide; Gass, Peter (Brain research. Molecular brain research, 2004)
The “neurotrophin hypothesis” of depression predicts that depressive disorders in humans coincide with a decreased activity and/or expression of brain-derived neurotrophic factor (BDNF) in the brain. Therefore, we investigated whether mice with a reduced BDNF expression due to heterozygous gene disruption demonstrate depression-like neurochemical changes or behavioral symptoms. BNDF protein levels of adult BDNF+/− mice were reduced to about 60% in several brain areas investigated, including the hippocampus, frontal cortex, striatum, and hypothalamus. The content of monoamines (serotonin, norepinephrine, and dopamine) as well as of serotonin and dopamine degradation products was unchanged in these brain regions. By contrast, choline acetyltransferase activity was significantly reduced by 19% in the hippocampus of BDNF+/− mice, indicating that the cholinergic system of the basal forebrain is critically dependent on sufficient endogenous BDNF levels in adulthood. Moreover, BDNF+/− mice exhibited normal corticosterone and adrenocorticotropic hormone (ACTH) serum levels under baseline conditions and following immobilization stress. In a panel of behavioral tests investigating locomotor activity, exploration, anxiety, fear-associated learning, and behavioral despair, BDNF+/− mice were indistinguishable from wild-type littermates. Thus, a chronic reduction of BDNF protein content in adult mice is not sufficient to induce neurochemical or behavioral alterations that are reminiscent of depressive symptoms in humans.